Drift-controlled design of reinforced concrete frame structures under distant blast conditions - Part I : theoretical basis - Li, Bing (2012)
Proper control levels of lateral drifts anticipated for reinforced concrete (RC) frame structures within the predefined performance level become crucial when the frame structure is subjected to distant intense surface explosions. For this purpose, a